1986
DOI: 10.1002/j.1460-2075.1986.tb04517.x
|View full text |Cite
|
Sign up to set email alerts
|

Excision of Ds produces waxy proteins with a range of enzymatic activities.

Abstract: The waxy (wx) locus of maize encodes an enzyme responsible for the synthesis of amylose in endosperm tissue. The phenotype of the Dissociation (Ds) insertion mutant wx‐m1 is characterized by endosperm sectors that contain different levels of amylose. We have cloned the Wx gene from this allele and from two germinal derivatives, S5 and S9, that produce intermediate levels of amylose. The Ds insertion in wx‐m1 is in exon sequences, is 409 bp in length and represents an example of a class of Ds elements that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(47 citation statements)
references
References 24 publications
(12 reference statements)
0
47
0
Order By: Relevance
“…Molecular cloning and characterization of the wx-ml mutation were reported previously (33). Relevant to this study is the fact that the allele contains a 409-bp Ds element in exon 9 of the Wx gene (Fig.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Molecular cloning and characterization of the wx-ml mutation were reported previously (33). Relevant to this study is the fact that the allele contains a 409-bp Ds element in exon 9 of the Wx gene (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Comparison of these sequences with the wx-ml sequence (33) permitted the precise determination of 5' and 3' splice sites. Southern blot analysis of PCR products was as described previously (33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is some evidence to suggest that GBSSI does interact with the amylopectin component of the starch granule. Studies of amylose-free mutants of several species which have inactive forms of GBSSI [22,23] have shown that GBSSI is still predominantly granule-bound, even though the granule lacks amylose. This suggests that the binding of wild-type GBSSI to starch granules may be largely or entirely due to an interaction with the amylopectin component rather than the amylose component of the granule.…”
Section: Discussionmentioning
confidence: 99%
“…The soluble extract was diluted 1 : 40 in gel sample buffer, heated to 90 mC for 2 min and loaded onto 6 % SDS/polyacrylamide gels. The gels were blotted on to nitrocellulose and the blots developed with antiserum to (A) pea GBSSI [22] (dilution : 1/2500) or (B) a truncated form of pea SSII [10] (dilution : 1/10 000). Lanes contained : 1, proteins from potato starch ; 2, E. coli cells transformed with pMUT6 and expressing mature potato GBSSI ; 3, E. coli cells transformed with pMUT13 and expressing mature pea SSII ; 4, E. coli cells transformed with the vector pET-3 alone ; and 5, proteins from pea starch.…”
Section: Figure 1 Expression Of Starch Synthases In E Colimentioning
confidence: 99%